Recombinant human thymosin beta‐4 (rhTβ4) improved scalp condition and microbiome homeostasis in seborrheic dermatitis. Issue 5 (28th July 2021) - Yu, Rui; Lin, Qingbin; Zhai, Yanfang; Mao, Yunyun; Li, Kai; Gao, Yuemei; Liu, Yanhong; Fu, Ling; Fang, Ting; Zhao, Mengsu; Guan, Lei; Hou, Lihua; et al.
Summary: Seborrheic dermatitis (SD) is a recurrent common inflammatory skin disease that affects all ethnic groups in all regions worldwide. However, no specific treatment or preventive measure is yet available. Identifying effective treatments with acceptable safety and tolerability is desirable. In this study, scalp microbiota alterations were measured in SD, showing significantly greater abundance of Malassezia and Staphylococcus and diminished fungal and bacterial diversity compared with healthy controls. We investigated the benefit of a 4‐week treatment with 0.5 mg ml ‐1 recombinant human thymosin β4 (rhTβ4) gel or 2% ketoconazole lotion on the scalp condition of 71 patients with SD compared with 21 healthy individuals. Clinical assessment (Adherent Scalp Flaking Score, and the Maximum Erythema Area) and physiological conditions (transepidermal water loss, hydration, and sebum secretion) were evaluated. The rhTβ4 treatment provided significantly greater efficacy than ketoconazole and a sustained effect in the treatment of scalp SD. More importantly, rhTβ4 dramatically improved the microbiome homeostasis and prompted a shift of scalp microflora towards healthy composition, helping symptoms and ameliorating physiological conditions more effectively and durably than ketoconazole. Our research demonstrated the scalp microbe dysbiosis of SD and highlighted rhTβ4 as a promising therapeutic strategy in the prevention and treatment of SD. Abstract : Our research demonstrated the scalp microbe dysbiosis of SD and highlighted rhTβ4 as a promising therapeutic strategy in the prevention and treatment of SD. A disequilibrium in the proportion of major bacterial and fungal populations, especially decreased microbiome diversity along with increased proportions of Malassezia and Staphylococcus species, is associated with SD. Besides, rhTβ4 could be a potential solution to lessen seborrheic dermatitis more effectively and in a more durable manner than ketoconazole, not only reducing symptoms but also improving and maintaining microbiome homeostasis.